Study of xT scaling in proton-proton collisions measured by the ALICE experiment - Pohjoisaho, Esko (2012)
In this Master's Thesis an analysis of proton proton data measured by the ALICE (A Large Ion Collider Experiment) Collaboration at center-of-mass energies 7 TeV and 2.76 TeV is presented. The ALICE detector is located at the LHC (Large Hadron Collider) at CERN, Switzerland. The goal of this thesis was to study whether the isolation requirement can increase the sensitivity of the xT spectra (xT=2pT/sqrt(s)) to higher-twist (HT) processes. In HT processes the outgoing hadron is produced directly in the hard subprocess, rather than in the fragmentation process described by the leading-twist (LT) processes in the perturbative QCD picture. Higher-twist processes are mainly low pT phenomena, causing steeper fall-off of the cross section distributions with respect to xT.